Analyzing Markets for Health Workers: Insights from Labor and Health Economics - McPake, Barbara (World Bank, 2015)
This publication is part of the Bank?s multiyear program to enhance its knowledge of HRH policies. The program?s ultimate objective is to strengthen knowledge and capacity to collect evidence, analyze, and evaluate the effectiveness of HRH interventions in the context of a country?s health system strengthening strategy. It specifically addresses the theoretical and empirical evidence on health labor markets in low- and middle-income countries. Health labor market analysis has much to contribute to resolving globally widespread HRH problems, and their continuing neglect provides some explanation for their persistence. Policy makers in countries promulgating or refining strategies for achieving universal health coverage will find it important to understand how key elements in their health labor market are likely to interact and how these interactions could help?or hinder?progress toward universal health coverage. These interactions are complex and multidimensional, and this publication highlights some areas where forces in the health labor market matter most.